Grid connection sizing of hybrid PV-battery systems: Navigating market volatility and infrastructure constraints - Samir Jeddi (Institute of Energy Economics at the University of Cologne (EWI), 2025)
The increasing share of intermittent renewable energy generation amplifies power price volatility, raising the need for storage technologies such as battery energy storage systems (BESS). However, limited transmission infrastructure, particularly constrained grid connections, poses a major barrier to the deployment of both BESS and further renewable generation. Co-locating BESS with wind and solar assets can increase grid connection utilization and lower project costs. This study examines the effects of grid connection rationing on hybrid PV-BESS systems, accounting for weather-induced generation uncertainty and price fluctuations. Findings indicate that PV and BESS margins exhibit a strong negative correlation, leading to risk diversification. Grid withdrawal constraints substantially reduce contribution margins and increase risk exposure by lowering the diversification effect. In contrast, hybrid PV-BESS systems can reduce their grid injection capacity by up to 60% of their nameplate capacity without significantly affecting contribution margins or risk, as peak solar generation coincides with low power prices. A market premium payment diminishes the diversification benefits of hybrid PV-BESS systems and encourages greater grid connections by inflating the value of generation during low-price periods. These findings suggest that the central features of the German EEG innovation tender scheme for hybrid BESS systems - grid withdrawal constraints and a market premium - created an unnecessary excess burden for taxpayers.
Keywords: C61; C63; D81; L51; Q41; Q42; 330; PV-battery storage; Grid constraints; Renewable integration; Diversification; Riskmitigation